Climate Change as a Social Determinant of Health: An Interactive Case-Based Learning Activity - Arindam Sarkar; Nital P. Appelbaum; Rathi Asaithambi; Connie Tran; Doris Lin; Anjali Aggarwal; Stephanie Nguyen (Association of American Medical Colleges, 2023)
Introduction Despite consensus on climate change's impact on humans, medical schools have not widely adopted inclusion of environmental topics into their mandatory curriculum. This educational activity explicitly addresses climate change as one of the environmental determinants of health (EDH). Methods We developed a required, 1-hour module for all first-year medical students. This interactive, case-based, small-group activity was incorporated into a curriculum within an advising program but could be run independently. Before and after the session, participants completed evaluations assessing knowledge gains and attitude shifts. Results Of 183 first-year students, 155 completed both pre- and postmodule surveys. Participants' rating increased on the postmodule survey item "priority should be given to the discussion of EDH in medical education." The Wilcoxon signed rank test determined this difference in priority was statistically significant (p < .001). Reported strengths of this activity included the cases, informative content on EDH, the video, the discussion, and highlighted EDH resources. Suggested areas for improvement included more information on how to apply concepts to clinical contexts, guidance on how to engage in EDH concepts, and more discussion time. As a result of the module, students planned to engage in recycling, reduced consumption, advocacy, and changes to mode of transportation. Discussion Climate change remains the greatest global threat to human health, and future physicians must be equipped to educate patients and policymakers on the harms of environmental hazards. This brief yet effective module offers one approach to incorporating this topic into medical school curricula.